A Study Of Spectrum Of Findings Of Magnetic ResonanceImaging In Ankle Joint Pathologies (Indian Journal of Applied-Basic Medical Sciences, 2021)
Aims & Objectives: This study is being carried out to describe various MRI features in the pathologies of ankle joint. Trauma to the ankle joint is a significant cause of morbidity in the young & active individuals especially amongst labourer’s, road traffic accident patients and athletes. A correct diagnosis regarding traumatic/ non traumatic ankle joint pathologies is essential for early operative as well as non-operative treatment. Magnetic resonance imaging (MRI) has now been accepted as the best modality for non-invasive evaluation of ankle pathologies. This study was undertaken to study different pathologies of ankle joint and its incidence by MR imaging.MATERIALS AND METHODS:A total of 50 cases of clinically suspected & diagnosed of having any pathology of ankle joint by MR imaging of the ankle, at the department of Radiodiagnosis, AMC MET Medical college, L.G hospital, Maninagar, Ahmedabad. Study was performed between December 2018 to December 2019. MRI was carried out on SIEMENS 1.5 T MAGNETOM_ESSENZA machineResults:Of the total50 patients evaluated, most common pathology of ankle joint being anterior talofibular ligament tear & tenosynovitis,20(40%) cases of each, followed by stress fractures 17(34%) & contusions 16(32%). Associated findings include joint collection, marrow edema &soft tissue changes.Interpretation and Conclusions:From these observations, it is found that MRI is an excellent, noninvasive, radiation free imaging modality with multiplanar capabilities and better soft tissue delineation. It can accurately detect, localize and characterize various ligamentous, tendinous, bony & soft tissue pathologies related to ankle joint and thereby guiding in further management of the patient.
Keywords: Spectrum; Magnetic Resonance Imaging; Ankle Joint Pathologies